Anatomy of Master Knot of Henry: A morphometric study on cadavers - Orhan Beger; Özlem Elvan; Mert Keskinbora; Burçin Ün; Deniz Uzmansel; Zeliha Kurtoğlu (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The objective of this study was to evaluate the features of flexor hallucis longus (FHL), flexor digitorum longus (FDL) and flexor digitorum accessorius (FDA) muscles with relevance to the tendon grafts and to reveal the location of Master Knot of Henry (MKH). Methods: Twenty feet from ten formalin fixed cadavers were dissected, which were in the inventory of Anatomy Department of Medicine Faculty, Mersin University. The location of MKH was identified. Interconnections of FHL and FDL were categorized. According to incision techniques, lengths of FHL and FDL tendon grafts were measured. Attachment sites of FDA were assessed. Results: MKH was 12.61 ± 1.11 cm proximal to first interphalangeal joint, 1.75 ± 0.39 cm below to navicular tuberosity and 5.93 ± 0.74 cm distal to medial malleolus. The connections of FHL and FDL were classified in 7 types. Tendon graft lengths of FDL according to medial and plantar approaches were 6.14 ± 0.60 cm and 9.37 ± 0.77 cm, respectively. Tendon graft lengths of FHL according to single, double and minimal invasive incision techniques were 5.75 ± 0.63 cm, 7.03 ± 0.86 cm and 20.22 ± 1.32 cm, respectively. FDA was found to be inserting to FHL slips in all cases and it inserted to various surfaces of FDL. Conclusion: The exact location of MKH and slips was determined. Two new connections not recorded in literature were found. It was observed that the main attachment site of FDA was the FHL slips. The surgical awareness of connections between the FHL, FDL and FDA, which participated in the formation of long flexor tendons of toes, could be important for reducing possible loss of function after tendon transfers postoperatively. Keywords: Flexor hallucis longus, Flexor digitorum longus, Flexor digitorum accessorius, Master knot of Henry, Slip, Tendon transfer